PEMBINAAN WANITA PENGOLAH IKAN ASIN DI PESISIR MUARA ANGKE JAKARTA UTARA - Nayu Nurmalia; Richard W.E Lumintang (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2006)
Women who were involved in processing salty fish at Muara Angke, north of Jakarta, had significant contribution to their salty fish business. So far, they had never been involved in any empowerment program offered either by government institution or by non government organization. Men were mostly involved in such empowerment activities. In this conjunction, the objectives of this study were: (1) to determine the skills of the women involved in salty fish processing, (2) to identify both the internal and external factors related to the women’s skills in processing salty fish, and (3) to determine the relationship intensity of the women’ skills in salty fish processing and their productivity in processing such fish. The findings of the study were: the women productivity in salty fish processing was significantly related to their skills in getting qualified fresh fish, in processing and drying salty fish, in book keeping and accounting, and in getting information on marketing system.